Methodological guidelines for geoheritage site assessment: A proposal for Serbia - Maran-Stevanović Aleksandra (Geološki Anali Balkanskoga Poluostrva, 2015)
Various minerals, rocks, soil types, ore and fossiliferous deposits, structural and tectonic elements, surface and subterranean landforms, all those natural phenomena representing geodiversity in a small scale contribute to our understanding the significant events and episodes of the geological history of the Earth. Intended methodology for qualitative and quantitative assessment is presented, including valuing criteria and their numerical indicators, which serve as analytical instruments to identify and select potential geoheritage objects in Serbia. Objective assessing and categorizing the geoheritage objects are the starting points for their rational utilization, adequate conservation, proper interpretation and promotion.